Fatigue damage severity assessment of RC beam - Md Nor, Noorsuhada; Mat Saliah, Soffian Noor; Ibrahim, Azmi; Mohd Saman, Hamidah; Muhamad Bunnori, Norazura (Emerald, 2019)
Purpose: The purpose of this paper is to present the investigation of damage severity of reinforced concrete (RC) beam subjected to increasing fatigue loading using intensity of acoustic emission (AE) signal. Design/methodology/approach: Together 17 RC beams with dimension of 150 × 150 × 750 mm were prepared. Third point loading fatigue test was performed based on load at the first crack (Pcr) and the ultimate static load (Pult). The frequency of 1 Hz was used with the increasing fatigue loadings, 0.5Pcr (P1), 0.8Pcr (P2), 1.0Pcr (P3), 0.2Pult (P4), 0.5Pult (P5) and 0.6Pult (P6). The damage severity of crack for each phase of loading allowed the identification of the crack modes of the beams, namely, Zone A (no significant emission), Zone B (minor), Zone C (intermediate), Zone D (follow-up) and Zone E (major). Findings: The intensity analysis indicated clear trend with respect to crack propagation in the beam and, hence, can be used to monitor the crack occurrence in the beam. Originality/value: The intensity analysis has been carried out for the beam subjected to increasing fatigue loading. The analysis was based on the AE data obtained from channel basis and located event. © 2019, Emerald Publishing Limited.